2018
DOI: 10.1016/j.tsf.2018.09.022
|View full text |Cite
|
Sign up to set email alerts
|

From sputtered metal precursors towards Cu2Zn(Sn1-x,Gex)Se4 thin film solar cells with shallow back grading

Abstract: Bandgap grading is often employed in thin film solar cell absorbers for creating the back surface field that can reduce interface recombination at the back contact. Here, we investigate different pathways to obtain back graded Cu 2 Zn(Sn 1-x ,Ge x)Se 4 thin film solar cells based on a co-sputtered metal precursor and rapid thermal annealing route. The absorber bandgap can be precisely tuned for the whole compositional range of x=0…1. While Ge does not accumulate towards the back in absorbers fabricated from un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 21 publications
1
10
0
Order By: Relevance
“…On the other hand, alloying approaches have been also investigated recently. As in the case of doping, Ge alloying of kesterite has immediately demonstrated a great potential, with device efficiencies ranging from 6.8 to 12.3% [114][115][116][117][118][119][120][121][122]. Among them, it is interesting to note that the best efficiency was achieved with a relative Ge content of 39% (i.e.…”
Section: Germanium (Ge)mentioning
confidence: 99%
“…On the other hand, alloying approaches have been also investigated recently. As in the case of doping, Ge alloying of kesterite has immediately demonstrated a great potential, with device efficiencies ranging from 6.8 to 12.3% [114][115][116][117][118][119][120][121][122]. Among them, it is interesting to note that the best efficiency was achieved with a relative Ge content of 39% (i.e.…”
Section: Germanium (Ge)mentioning
confidence: 99%
“…Ge has been revealed to naturally accumulate at the back region of the CZTGSe absorber with a demonstrated increased band gap, in a similar fashion to Ga in CIGS. 54 The accumulation of Ge at the back interface of kesterite films has previously been reported, 45 and no promising steps such as solar cell improvement attributable to the presence of the back surface field (BSF) was reported. In that regard, this work demonstrates for the first time that deliberate band engineering can lead to improved photovoltaic performances.…”
Section: ■ Introductionmentioning
confidence: 99%
“…A 50 nm thick Ge layer was deposited on top of the metal precursor, but preferential Ge diffusion towards the back interface was observed after selenization. In a recent study, elemental targets were co‐sputtered to fabricate CZGTSe devices with shallow Ge grading from both graded and stacked precursors . Unlike in the work by Márquez et al, no preferential accumulation of Ge near the back contact was observed.…”
Section: Introductionmentioning
confidence: 99%